Activity-Based Costing in Determining Competitive Pricing Strategies - Firayani Firayani; Liza Ulfiana (PT. Hafasy Dwi Nawasena, 2025)
Competitive pricing requires firms to rely on accurate cost information, particularly as production and service activities become increasingly complex. This study aims to analyze the role of Activity-Based Costing in supporting firms to formulate competitive pricing strategies. A systematic literature review was employed, involving searches across international and national databases, application of inclusion criteria based on scientific rigor, and critical appraisal of selected studies. The selection process followed PRISMA guidelines and resulted in 28 eligible articles. The findings indicate that activity-based costing methods enhance cost accuracy, identify both value-adding and non-value-adding activities, and reveal cost distortions commonly found in traditional costing systems. The results further show that firms integrating activity-based cost information into their pricing policies tend to achieve more rational pricing structures, more stable profitability, and stronger competitive positions. In conclusion, Activity-Based Costing provides substantial strategic value for pricing decisions; however, its effectiveness relies heavily on the accuracy of activity data and the organizational readiness to implement the approach consistently.